Penerapan Model Pembelajaran Berbasis Masalah dalam Pembelajaran Menulis Teks Eksplanasi - Wati, Maulida Laily Kusuma; Haryadi; Haryati, Nas (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
This study was a qualitative descriptive study to describe the design and implementation of problem-based learning models and determine the teachers' obstacles in teaching explanation text of the eleventh grade at SMK Negeri 3 Kudus. The subjects of this study were teachers and eleventh-grade students of SMK Negeri 3 Kudus. The methods of data collection in this study were observation and interview records. The collected data were analyzed using descriptive methods. The research's findings are that teachers arrange problem-based learning models in the lesson plan based on the components of the 2013 curriculum. Secondly, teachers apply problem-based learning models that conform to problem syntax. Third, the obstacles encountered when applying problem-based learning models to teach explanation text came from the teacher's experience in identifying interesting topics and the teacher's ability in the time management needed for learning because this learning model requires a longer time. From the student's point of view, more attention is needed to describe the differences in student abilities. Further, the lack of ability to think critically becomes a challenging obstacle for teachers because the problem-based learning model requires students to be able to think critically.